Exploring the critical success factors of value management for sustainable public housing in Malaysia: findings from a preliminary study / Muhammd Shahfarhan Mohamad Yassin ... [et al.] - Mohamad Yassin, Muhammd Shahfarhan; Jaapar, Aini; Marhani, Mohd Arif; Ahmad Bari, Nor Azmi (College of Built Environment, 2023)
National Housing Policy (NHP) 2018-2025 emphasizes the need of improving quality and sustainability in Malaysian housing development (MHLG, 2018).